(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The review is devoted to the analysis of ways to influence hemostasis in order to improve the prognosis of patients with chronic coronary heart disease (CHD). The results of the most significant randomized clinical trials evaluating the effectiveness and safety of dual antiplatelet therapy in the treatment of patients with chronic ischemic heart disease are discussed. The use of rivaroxaban in addition to acetylsalicylic acid (ASA) to reduce the risk of cardiovascular events in patients with chronic ischemic heart disease is justified.